Post-dural puncture headache - S.M. Byshovets (Медицина неотложных состояний, 2023)
The problem was analyzed and the pathophysiology of post-dural puncture headache was highlighted. Clinical manifestations, risk factors and diagnosis of this complication are given. Modern methods for the treatment of post-dural puncture headache are described. The own experience on the prevention of this problem was made public with the conclusion that when using Ball-Pen needles, only 12 (0.56 %) of 2125 patients complained of post-dural puncture headache, which is 12.5 times less than the average statistical indicators.